THE DEPENDENCE OF MORPHOLOGICAL AND PHYSIOLOGICAL INDICATORS OF THE LEAVES OF WOODY PLANTS ON THE DEGREE OF TECHNOGENIC POLLUTION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
Plants of modern urban ecosystem suffer from negative effects of a series of technogenic pollution which leads to changes in their morphological and physiological state. The reason for this is the penetration of phytotoxicants into plant organs, primarily, into leaves, thus distorting the structural components of cells and their functioning. In various species the degree of this reaction is manifested differently, so this fact must be taken into consideration when creating environmentally effective plantations. For this purpose the integrated study of the impact of pollutants on the morpho-physiological state of deciduous trees was conducted. Some morphological, physiological and biochemical indicators of leaves of Tilia cordata Mill., Populus tremula L., Salix fragilis L., Salix alba L. from different urban areas, characterized by different levels of technogenic pollution, were also studied. It was found out that the increase of technogenic load led to the decrease in the size of leaves, the increase of their necrotization and the total ash content of the tissues of these organs as well as the reduction of the photosynthetic pigments concentration with increase of relative portion of carotenoids which is the most significantly revealed in the leaves of the lime-tree, brittle willow and, to a lesser extent, in the white willow. At the same time the increased relative portion of carotenoids in the photosynthetic organs in case of strong pollution by pollutants indicates an increase of the protective role of the yellow pigment. Besides, the increased ratio of chlorophyll a/b characteristic for the resistant plant species was established in the leaves of these trees, which is a sign of a higher potential photochemical activity of leaves and the rate of photosynthesis.All the studied morpho-physiological indicators characterize a greater resistance to pollutants of Tilia cordata, Salix fragilis, Salix alba, which can be recommended for the reconstruction of the sanitary and protective plantations of Arzamas. The studied tree species have a great capacity of gettering harmful technogenic substances with a further effective ability to accumulate them in the tissues of the leaves.